Formulasi Dan Uji Stabilitas Hair Tonic Kombinasi Ekstrak Daun Pandan Wangi (Pandanus Amaryllifolius Roxb.) Dan Vco - Tamarin, Laura; Ulfa, Ade Maria; Nofita, Nofita (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Hair loss affects up to 50 million people in the United States and 20 million of them are women. Hair tonic is a cosmetic product that can prevent hair damage and loss. Fragrant pandan leaves (Pandanus amaryllifolius Roxb.) has the potential to overcome hair loss because it contains antioxidant compounds, namely alkaloids, tannins, saponins and others. Apart from that, VCO also has the potential to treat hair damage because it contains fatty acids, vitamin K, vitamin E, etc. The aim of this research is to make preparations hair tonic which contains fragrant pandan leaf extract and VCO then tested for physical evaluation and determined the stability of the preparation hair tonic. Extraction was carried out using the maceration method using 96% ethanol solvent, stability testing using the method cyling test and the stability test results were analyzed using Sample Paired T-Test. The yield of fragrant pandan leaves was 11.04%. Hair tonic made into 3 variations FI(2.5%:2.5%), F2(5%:2.5) and F3(7%:2.5%). The test results showed that all dosage formulations met the physical evaluation requirements in the homogeneity, pH and viscosity tests in accordance with SNI 19-4955-1998, however the specific gravity test before storage did not meet the physical evaluation requirements of the dosage form because it was ˃1 g/ml. Preparation hair tonic F0, F1 and F2 are statistically stable in storage with organoleptic test parameters, pH, homogeneity, specific gravity, viscosity and irritation test because the sig value is> 0.05, while F3 experiences instability in the specific gravity test because the sig value is <0.05.